A study of serum prolactin in dermatological diseases in a tertiary care hospital of Assam - Talukdar C; Boro B (Journal of Medical and Scientific Research)
Background: Prolactin functions as a neuroendocrine modulator of the skin immune system and epithelial cell proliferation. Prolactin and the immune system inter relationship have been studied extensively and opened new avenues in the field of immunoendocrinology. Prolactin may have an important role in some dermatological diseases like psoriasis, alopecia areata, and vitiligo. We aim to estimate serum prolactin values in patients of psoriasis, alopecia areata and vitiligo and compare it with healthy controls and also evaluate the correlation between serum prolactin levels and severity of the diseases.